SOCIALLY INTELLIGENT PROJECT MANAGER;SOFT SKILLS THAT PREVENT HARD DAYS - KIM WASSON (BERRETT-KOEHLER, 2020)
"This no-nonsense guide to social intelligence for project managers gives you a step-by-step process for building a bulletproof project team-no matter what gaps exist in personality, geography, culture, or communication style"--